INVESTIGATING THE IMPACT OF CRISIS ON CORPORATE COSTS AND SALES USING ECONOMETRICS METHOD - Heydari, Mohammad; Xiaohu, Zhou; Lai, Kin Keung; Yuxi, Zheng; Chen, Lin (Proceedings of National Aviation University (archive), 2019)
Background: this article seeks to complement the previous literature and clarify the importance of paying attention to the acceleration of globalization, and the global economic crisis that all countries will be affected directly and indirectly, through the crisis is important for the companies and one way out of the crisis, manages the marketing costs. Aim: this article seeks to identify the determinants, to find the Impact of Crisis on Corporate Costs and Sales with the using dynamic panel econometrics method and also, finding crisis effect on the costs and sales of companies. Setting: this article examines the effect of marketing costs on net sales; data from the 25-company’s active in the Tehran Stock Exchange (TSE) during 11 years (2002-2012) have been used. Methods: in order to test the hypothesis of the research, we analyze the information by econometric methods. In this research econometrics methods are respectively: (Panel data, static panel data, fixed effects, and random effects, fixed effects model, random effects model, Hausman test, static panel data model, dynamic layout data, Wald test). Also, it should be noted for data analysis in this research we used from (F Lieber test and Hausman test and Wald test). Software used in this study was Stata software, the first order difference method is used to eliminate the static effects, and the interrupted values of the dependent variable are used as tool variables. Results: research hypothesis test results shows the first and second researcher hypothesis is confirmed and the zero hypotheses are rejected. Also, the third and fourth and fifth researcher hypothesis is rejected, and the zero hypotheses are confirmed. Conclusion: the results indicate a significant impact on net sales of company’s marketing costs estimates indicate that costs 1 Rial in marketing, leading to increased sales of 58 Rials, and even during the global economic crisis, this figure is equivalent to 26 Rials. The analyses notice the importance of marketing expenditures on sales in Iran. Especially during the crises periods and after, marketing expenditures are found as having significant effects on sales.